The Effect of Financial Distress Model Altman Z-Score on Stock Prices in Food and Companies Beverages Listed on the Indonesian Stock Exchange Period 2017-2021 - Ananda, Fahira Trie; Sudarijati; Kartini, Tini; Zakaria, Nadisah; Harini, Sri (MultiTech Publisher, 2024)
The capital market has an important role in supporting a country's economy because the capital market has two functions at once, namely the economic function and the financial function. The capital market is a meeting place between parties who have excess funds (investors) and parties who need funds (companies) by buying and selling securities. The presence of the capital market has an important role for investors, both individual investors and business entities. They can channel the excess funds they have to invest, so that entrepreneurs can obtain additional capital funds to expand their business network from investors in the capital market. Issuers are parties conducting public offerings or companies that obtain funds through the capital market, both private and state-owned companies that seek capital from the stock exchange by issuing securities such as bonds, rights issues, warrants or shares (Malkan et al., 2021).